공공병원 실습 경험이 의대생의 공공보건의료 역량, 진로 인식, 교육 요구도에 미치는 영향 - 차봉은; Bongeun Cha; 김송림; Songrim Kim; 박경혜; Kyung Hye Park; 박귀화; Kwi Hwa Park; 윤소정; So Jung Yune (의료커뮤니케이션, 2024)
Purpose : Public health practicum opportunities in Korean medical schools remain limited, with scarce systematic research examining their educational impact. This study investigates the influence of public hospital practicum experiences on medical students’ public health competencies, career perspectives, and educational needs. Methods : A survey was conducted on the perceived importance and current achievement level of public health competencies, as well as career awareness, among 163 third- and fourth-year medical students from two medical schools in South Korea that operate public hospital practicum programs and two that do not. The survey tool, rigorously developed through literature review and expert validation, underwent analysis using independent and paired samples t-tests, crosstabulation, Borich needs analysis, and the Locus for Focus model. Results : Results indicated no significant differences in the competency levels of public healthcare skills between students with and without public hospital practicum experience. However, students with practicum experience in public hospitals demonstrated a greater inclination to engage in programs led by public healthcare organizations and to consider a career in public healthcare. Moreover, compared to those without practicum experience, students with such experience were more likely to report intentions to address community public health challenges and to assess public health policies aimed at these issues. Conclusion : This study provides meaningful insights into the differential career orientation and educational needs shaped by public hospital practicum experiences, underscoring the implications for enhancing public health practicum education.